FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ratih Putri Ariesmaya, 09.05.52.0087; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of Return On Equity (ROE), Net Profit Margin (NPM), Earning Per share (EPS), and Cash Ratio of stock price category LQ-45 companies listed on the Indonesia Stock Exchange (IDX). The population is the entire company LQ-45 in Indonesia Stock Exchange (IDX) with 45 companies and research during the period of 2009 to 2011. Samples taken in this study is 25 companies. The sampling technique used purposive sampling. The analytical tool used in this study is Multiple Linear Regression Analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 83,6%. As for the test statistic F-test showed that, between Return On Equity (ROE), Net Profit Margin (NPM), Earning Per share (EPS), and Cash Ratio jointly influence on stock prices. Partial results of hypothesis testing indicates that there is a positive effect of the Return On Equity (ROE) and Earning per share (EPS) of the stock price. As for the Net Profit Margin (NPM) and the Cash Ratio indicates a negative effect on stock prices.Keywords: Return On Equity (ROE), Net Profit Margin (NPM), Earning Per share (EPS), Cash Ratio and Stock Price